Long Non-coding RNA LINC01119 Promotes Neuropathic Pain by Stabilizing BDNF Transcript - Zhang, Le; Feng, Hao; Jin, Yanwu; Zhan, Yufeng; Han, Qi; Zhao, Xin; Li, Peilong (Frontiers in Molecular Neuroscience, 2021)
Neuropathic pain (NP) is caused by primary injury or dysfunction of the peripheral and the central nervous system. Long non-coding RNAs were critical regulators involved in nervous system diseases, however, the precise regulatory mechanism remains unclear. This study aims to uncover the essential role of LINC01119 in NP progression and further clarify the underlying regulatory mechanism at post-transcriptional level. LINC01119 was significantly upregulated in rats of spare nerve injury (SNI) group compared to sham group. Functionally, silencing of LINC01119 significantly alleviated the neuropathic pain-induced hypersensitivity and reduced the increase in IL−6, IL−1β, and TNF−α caused by SNI. Mechanistically, Brain-derived neurotrophic factor (BDNF) was identified as the functional target of LINC01119. Besides, an RNA binding protein, ELAVL1 could directly interact with LINC01119, and this formed LINC01119- ELAVL1 complex binds to BDNF mRNA, strengthening its RNA stability and increasing the expression level of BDNF at both transcript and protein levels. Clinically, serum LINC01119 was verified as a promising diagnostic biomarker for NP patients. LINC01119 induces NP progression via binding with ELAVL1 and increasing BDNF mRNA stability and expression level. Therefore, LINC01119 may serve as a promising diagnostic marker and therapeutic target for NP treatment.